Estimating foot‐and‐mouth disease (FMD) prevalence in central Myanmar: Comparison of village headman and farmer disease reports with serological findings. Issue 2 (10th November 2019) - van Andel, Mary; Jones, Geoff; Buckle, Kelly; Phiri, Ben; McFadden, Andrew; Dacre, Ian; Bingham, Paul; Heuer, Cord; Abila, Ronel; Win, Htun Htun; Lwin, Khin Ohnmar; Binney, Barbara; et al.
Abstract: The impacts of foot‐and‐mouth disease (FMD) on food security in developing countries are difficult to quantify due to the scarcity of accurate data on the prevalence and incidence of affected villages. This is partly due to resource constraints as well as the logistical challenges of conducting regular diagnostic testing in remote locations. In this study, we used descriptive analysis and latent class analysis (LCA) models to analyse data collected during a field survey of 160 villages in central Myanmar in the Mandalay and Sagaing Regions over the 2012–2016 time period. We evaluated the performance of verbal reports made by village householders and headmen against serological data to retrospectively determine the FMD‐infection status of our study area and to identify factors contributing to under‐reporting. Blood samples were collected from approximately 30 cattle per village in both the 6‐ to 18‐month age range and over 18‐month age range to distinguish between recent and historic exposure. Village householders were asked to identify pictures of FMD‐affected cattle amongst pictures of cattle affected with other common endemic diseases to assess the accuracy of their verbal reporting. The serological results confirmed that FMD is endemic in central Myanmar with village‐level seroprevalence estimated at 56% for animals 6–18 months of age and 80% when all age groups were considered together. Most village householders were familiar with the clinical signs of FMD‐affected cattle (72%). Based on the results from the LCA models, the village headman had a sensitivity of 77% and specificity of 75% for identifying FMD outbreaks in their village, whereas individual householders had a higher sensitivity and lower specificity of 80% and 56%, respectively. The level of disagreement between the different sources was correlated with the total number of cattle in the village and may potentially be worse in villages where endemic FMD may have led to a high level of natural immunity in cattle and subsequent masking of clinical signs. However, other regional effects such as the intensity of FMD extension efforts cannot be ruled out. Overall, the results suggest that verbal reports of FMD outbreaks from village headmen may be a useful tool to integrate into active FMD surveillance programmes in developing countries.